2019
DOI: 10.1093/jxb/erz119
|View full text |Cite
|
Sign up to set email alerts
|

Secondary sulfur metabolism in cellular signalling and oxidative stress responses

Abstract: Secondary sulfur metabolism produces several metabolites which regulate various aspects of cellular signalling and homeostasis in response to environmental perturbations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 125 publications
0
42
0
1
Order By: Relevance
“…Line C had highest expression of this gene, followed by A; with B having significantly lower expression overall (Figure 6). Previous studies have shown that SLIM1 down regulates APK gene expression and GSL biosynthesis as a way of conserving sulfur for primary metabolism (Chan et al, 2019). Our data suggest that this is only the case between SLIM1a and APK3 (r = −0.597, q < 0.001; Supplementary Data File 1).…”
Section: Sulfur Metabolism Transcription Regulation and Transport Gmentioning
confidence: 47%
See 2 more Smart Citations
“…Line C had highest expression of this gene, followed by A; with B having significantly lower expression overall (Figure 6). Previous studies have shown that SLIM1 down regulates APK gene expression and GSL biosynthesis as a way of conserving sulfur for primary metabolism (Chan et al, 2019). Our data suggest that this is only the case between SLIM1a and APK3 (r = −0.597, q < 0.001; Supplementary Data File 1).…”
Section: Sulfur Metabolism Transcription Regulation and Transport Gmentioning
confidence: 47%
“…Also of note is that expression of MYB28 genes were positively associated with expression of SDI1 gene copies. Previous research has shown that the SDI1 protein binds to MYB28, inactivating expression and reducing GSL biosynthesis (Chan et al, 2019). In E. sativa the opposite appears to be true, with significant positive correlations between respective expression of two MYB28 copies and MYB29 with SDI1 copies (SDI1a and MYB29, r = 0.72; SDI1b and MYB28a, r = 0.507; SDI1c and MYB28c, r = 0.459; Supplementary Data File 1).…”
Section: Glucosinolate-related Transcription Factorsmentioning
confidence: 92%
See 1 more Smart Citation
“…SAM is also an important precursor for the synthesis of a group of essential metabolites including ethylene, vitamin B1, and polyamines (see Figure 1 in main text) [74,75]. PAPS has critical roles in cellular signaling and oxidative stress responses in providing activated sulfate for the sulfation of various metabolites in the secondary S metabolism including GSLs, hormones, growth-regulating peptides, and xenobiotic metabolism by sulfotransferases (SOTs) [9,76,77]. relative requirement being mirrored in the S concentration of their seeds [6].…”
Section: How Plants Cope With S Deficiencymentioning
confidence: 99%
“…Sulfur plays an important role in metabolism, for example the sulfur-containing amino acids methionine is required for protein biosynthesis and cysteine is an indispensable precursor of glutathione, which is crucial to cellular redox tuning [35]. Sulfur shortage caused apparent raise in ROS level (Fig.…”
Section: The Physiological Acclimation Of C Zofingiensis To Sulfur-smentioning
confidence: 99%